Forensic biomechanics - Kieser, Jules; Taylor, Michael, 1953 September 18-; Carr, Debra D.; Wiley eBooks (Chichester, West Sussex, UK : Wiley-Blackwell, 2012)
"The book not only provides an in-depth examination of the field of trauma biomechanics, but also discusses the role of biomechanical principles in the analysis of blood-splatter patterning, assault and child abuse, ballistics and the investigation of the fracture of fibers and textiles"--Provided by publisher.
Basic principles of biomechanics -- Biomechanics of bone and bony trauma -- Biomechanics of skin and soft tissue trauma -- The mechanics of bloodstain pattern formation -- Fibres and textiles.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Biomechanics; Forensic sciences -- Methodology; MEDICAL -- Sports Medicine; Biomechanics; Human mechanics; Biomechanics; Forensic Sciences -- methods; Wounds and Injuries -- pathology; Electronic books